Door in the Mountain : New and Collected Poems, 1965-2003. - Valentine, Jean. (Middletown : Wesleyan University Press, 2011)
The collected works of one of America's most innovative poets.
The Child JungColtrane, Syeeda's Song Flute; Photograph of Delmore Schwartz; The Torn-Down Building; Moon Man; The Child and the Terrorist, the Terrorist and the Child; Night; Pilgrims; Ordinary Things (1974); I; After Elegies; 'Autumn Day'; He Said; Forces; Kin; Anesthesia; After Elegies (2); II; 3 A.M. in New York; Space; Letter from a Country Room; A Child's Death; Revolution; Three Voices One Night in the Community Kitchen; The Knife; Seeing L'Atalante; III; "Twenty Days' Journey" by Huub Oosterhuis, Translated from the Dutch with Judith Herzberg; IV; This Hate; This Minute.
Couvre-Feu: After Paul Eluard.
Print version record.
eBooks on EBSCOhost
Keywords: American poetry -- 20th century; American poetry -- Women authors; Poésie américaine -- 20e siècle.; POETRY -- American -- General; American poetry; American poetry -- Women authors; 1900-1999; Electronic book